Labor Market Discrimination Against Hispanic and Black Men - Reimers, Cordelia W. (The Review of Economics and Statistics, 1983)
H ISPANIC American men have lower average wage rates than white non-Hispanics. In 1975 the average white non-Hispanic male wage-earner in the United States earned $5.97 an hour. Mexican men earned $4.31, 72% as much as white non-Hispanics; Puerto Rican men earned $4.52, 76% as much; and Cuban men earned $5.33, 89% as much as white non-Hispanics. By way of comparison, black men's average wages in 1975 were $4.65, 78% of the white male wage.' Several possible reasons for the Hispanics' lower wages come to mind. Among them are age and education, geographic location, immigration, language difficulties, and discrimination. For example, as shown in table 1, Mexicans and Puerto Ricans are younger, on average, than the white non-Hispanic population, and earnings tend to rise with age. Hispanics have lower average levels of education than white non-Hispanics, and wages are positively associated with education. Many Mexican Americans live in the Southwest, where prices are relatively low. Moreover, Hispanics are more likely to be recent immigrants and to lack fluency in English than white non-Hispanics, and so to be at a disadvantage in the labor market. In addition, there is a widespread belief that Hispanics suffer from employment discrimination, and cannot obtain the wages that their human capital would command if they were non-Hispanic whites. How much of the wage differentials described above are due to each of these factors, and to other inter-group differences in wage-related characteristics? In particular, how much impact does labor market discrimination have on the average Hispanic man's wage and how does this compare with discrimination against blacks? This paper provides answers to these questions. A few other efforts have been made to analyze the relative earnings of Hispanic and white nonHispanic men, using 1960 and 1970 Census data (Fogel, 1966; Poston and Alvirez, 1973; Poston, Alvirez, and Tienda, 1976; Long, 1977; and Gwartney and Long, 1978). We use more recent data from the 1976 Survey of Income and Education. This data set enables us to measure wage rates more accurately and to specify the wage function more completely than does the Census. Unlike previous analysts, in estimating the wage function we take account of possible selectivity bias due to the distinction between average wage offers and average observed wages. Thus, we hope to obtain a more accurate and up-to-date measure of labor market discrimination against Hispanic men. Section II explains the method used to separate the minority-white non-Hispanic wage differential into the portions due to differences in average characteristics and the portion due to differences in unobserved factors and discrimination, taking into account the possibility of selectivity bias in the observed wage sample. Section III describes the data used in the study and the specification of the wage equation. The breakdown of the observed wage differentials into components due to differences in participation in the wage and salary sector, local price levels, average characteristics, and discrimination are presented in section IV. Section V summarizes our findings and discusses their implications for efforts to improve the economic situation of Hispanics in the United States.